ACQUISITION: PROCESS, STRATEGY, PROBLEM IN FOREIGN LANGUAGE LEARNING - Ahmad Syafi’i (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
This paper explained the pattern of overcoming difficulties of foreign language learning, identifying based one previous study in learning English as a foreign language. Yet, it also shows general strategies that are useful to overcome the difficulties of acquiring a foreign language based on processability theory. Then, it examines that for learning a foreign language, as the learners need proper time and good management; however, the concept reveals need to focus that teacher’s role, learning methods, and strategies are advised. As the previous study shows of authentic material motivated leaners to improve their focus study in a foreign language as a subject.Keywords: process language learning, language Acquisition, language skill, proccessability theory.